2013
DOI: 10.1007/978-1-62703-776-1_22
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-Resolution Fluorescence Electron Microscopy (Nano-EM) in Cultured Cells

Abstract: Nano-resolution fl uorescence electron microscopy (nano-fEM) pinpoints the location of individual proteins in electron micrographs. Plastic sections are fi rst imaged using a super-resolution fl uorescence microscope and then imaged on an electron microscope. The two images are superimposed to correlate the position of labeled proteins relative to subcellular structures. Here, we describe the method in detail and present fi ve technical advancements: the use of uranyl acetate during the freeze-substitution to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…The small size of synaptic vesicles makes it difficult to assess behavior of the fusion pore, and previous work has reported multiple modes of synaptic vesicle fusion (Pyle et al 2000;Staal et al 2004;Harata et al 2006;Balaji and Ryan 2007;Zhang et al 2009;Park et al 2012;Bao et al 2018;Chanaday and Kavalali 2018). However, stable fusion pores were not detected by time-resolved electron microscopy (Watanabe et al 2014a;Watanabe et al 2014b). The concentration of a-synuclein at synapses (Maroteaux et al 1988;Iwai et al 1995;Withers et al 1997;Fortin et al 2004) nonetheless suggests that it may contribute to the rapid synaptic vesicle collapse observed in wild-type neurons.…”
Section: Mechanism For Pore Dilationmentioning
confidence: 99%
“…The small size of synaptic vesicles makes it difficult to assess behavior of the fusion pore, and previous work has reported multiple modes of synaptic vesicle fusion (Pyle et al 2000;Staal et al 2004;Harata et al 2006;Balaji and Ryan 2007;Zhang et al 2009;Park et al 2012;Bao et al 2018;Chanaday and Kavalali 2018). However, stable fusion pores were not detected by time-resolved electron microscopy (Watanabe et al 2014a;Watanabe et al 2014b). The concentration of a-synuclein at synapses (Maroteaux et al 1988;Iwai et al 1995;Withers et al 1997;Fortin et al 2004) nonetheless suggests that it may contribute to the rapid synaptic vesicle collapse observed in wild-type neurons.…”
Section: Mechanism For Pore Dilationmentioning
confidence: 99%
“…For brain tissue, very thin sections under fixed conditions have to be prepared (Dani et al, 2010). An active area of research is to adapt EM sample preparation methods to produce resin-embedded ultrathin sections for LBM imaging (Brown et al, 2010;Micheva and Smith, 2007;Watanabe et al, 2011Watanabe et al, , 2014Yao et al, 2011). Such an approach has many advantages: it improves the z resolution, as section thicknesses are typically 100 nm or less, it eliminates most background fluorescence and light aberration that are associated with thicker samples and it usually achieves a high degree of structural preservation.…”
Section: The Sample Preparation Methodsmentioning
confidence: 99%
“…Inspired by the array tomography sample preparation method (Micheva and Smith, 2007;Punge et al, 2008;Watanabe et al, 2011Watanabe et al, , 2014, we have developed a procedure to section intact brain samples embedded in the LR White acrylic resin into ultrathin (50-500 mm) sections, which allows for LBM imaging. To achieve a high level of Nyquist resolution, we typically label our samples using genetic tagging methods with PA-FPs, such as mEos2 (McKinney et al, 2009).…”
Section: Synapsementioning
confidence: 99%
“…Light microscopy after embedding can be performed on the whole block using confocal microscopy or on the cut sections either on EM grids or coverslips. The EM sample preparation protocol is modified to preserve fluorescence in the resin, but obtaining high‐quality LM data is more challenging than with conventional approaches due to some loss of fluorescence signal, and to autofluorescence properties of the resin . The advantage of this method is that exactly the same state of the specimen is imaged with both LM and EM.…”
Section: Overview Of Clem Techniquesmentioning
confidence: 99%
“…Combined with the suboptimal optical properties of the resin, this makes it challenging to introduce super‐resolution methods into CLEM protocols. Nevertheless, recent studies have shown that super‐resolution microscopy can be performed on resin‐embedded samples both with standard and specially designed FPs as well as with organic dyes . Additional adjustments of sample preparation protocols are required to achieve good imaging quality.…”
Section: Overview Of Clem Techniquesmentioning
confidence: 99%